The effect of background music towards Malaysian consumers’ shopping behavior in retail store - Ahmad Mustaqim Rohaizat, 1994-, author 618985; Zuraidah Sulaiman, supervisor 598934; Sekolah Perniagaan Antarabangsa Azman Hashim 617120 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Pengurusan (Pemasaran)) - Universiti Teknologi Malaysia, 2019